A Review on the Sustenance of Fashion Businesses during COVID-19: Impacts on Women Workers - Solomon Marfo Ayesu; Christiana Konamah Okai-Mensah; Beauty Awusi Nyavor Akporyo; Sophia Panarkie Pardie Ocran; Mohammed Ibrahim (Fashion and Textiles Review)
Purpose: This study investigates the impact of the COVID-19 pandemic on the fashion industry, focusing on how it has affected women workers. It aims to analyse the current state of the fashion business, highlighting the challenges faced due to economic difficulties, including factory closures and reduced consumer preferences.